Metadata and Semantic Research 4th International Conference, MTSR 2010, Alcalá de Henares, Spain, October 2010, Proceedings - Sanchez-Alonso, Salvador.; Sanchez-Alonso, Salvador.; Athanasiadis, Ioannis N.; Athanasiadis, Ioannis N. (Communications in Computer and Information Science,, 2010)
Metadata and semantic research is a growing complex ecosystem of conceptual, theoretical, methodological, and technological frameworks, offering innovative computational solutions in the design and development of computer-based systems. Within this perspective, researchers working in the area need to further develop and integrate a broad range of methods, results, and solutions coming from different areas. MTSR has been designed as a forum allowing researchers to present and discuss specialized results as general contributions to the field. This volume collects the papers selected for presentation at the 4th International Conference on Metadata and Semantic Research (MTSR 2010), held in Alcala de Henares––a world heritage city and birthplace of Miguel de Cervantes––at the University of Alcala (October 20–22, 2010). The first MTSR conference was held online in 2005, followed by two more editions: in Corfu (2007) and in Milan (2009). The experience acquired during the past five years, and the warm welcome of MTSR by the research community, encouraged us to organize this new edition of the series, and turn it into a yearly event. According to the number and quality of the contributions submitted for revision, our 2010 effort was again a considerable success.